Study of the evolutionary origin and virulence factors of bacterial species causing umbilical cord infections in newborns - Riyadh Al-Mousawi, Rehab; Abdul Wahid Al-Kaabi, Wafaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The umbilical cord is a vital physiological structure that connects the fetus to the placenta. It plays a pivotal role in the exchange of oxygen, nutrients, and waste between the mother and fetus during pregnancy. This study aimed to identify bacterial isolates from newborns with umbilical cord infections in Baghdad Governorate. One hundred swabs were collected from newborns with umbilical cord infections who visited the pediatric consultants at Al-Kadimiya Teaching Hospital and Al-Karkh Hospital. The swabs ranged in age from 3 days to 28 days and were of both sexes. The study was conducted from October 1, 2024, to February 1, 2025. Phenotypic and biochemical results revealed that 100 samples were isolates, of which 29.16 were identified as Staphylococcus aureus, 29.16 were identified as Escherichia coli, 29.16 were identified as Pseudomonas, 8.33 were identified as Enterococcus, and 4.16 were identified as Bacteroides. Molecular screening was performed using PCR. Biofilm production results also showed a significant decrease in the number associated with biofilm formation, indicating that the bacterial species is directly proportional to the isolate type and sample collection time. DOI: https://doi.org/10.54633/2333-024-056-003